2002
DOI: 10.1074/jbc.m111993200
|View full text |Cite
|
Sign up to set email alerts
|

Defective Oligomerization of Arylsulfatase A as a Cause of Its Instability in Lysosomes and Metachromatic Leukodystrophy

Abstract: In one of the most common mutations causing metachromatic leukodystrophy, the P426L-allele of arylsulfatase A (ASA), the deficiency of ASA results from its instability in lysosomes. Inhibition of lysosomal cysteine proteinases protects the P426L-ASA and restores the sulfatide catabolism in fibroblasts of the patients. P426L-ASA, but not wild type ASA, was cleaved by purified cathepsin L at threonine 421 yielding 54-and 9-kDa fragments. X-ray crystallography at 2.5-Å resolution showed that cleavage is not due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 24 publications
1
43
0
1
Order By: Relevance
“…4). At both pH values, neither protein UV peaks nor sulfatase activities provided any indication for dimerization or oligomerization of ASG as described for its closest relative, arylsulfatase A (30). ASG eluted as a 63-kDa protein, which corresponds to the monomeric molecular mass also observed in SDS-PAGE.…”
Section: Asg Is Active In the Monomericmentioning
confidence: 72%
See 1 more Smart Citation
“…4). At both pH values, neither protein UV peaks nor sulfatase activities provided any indication for dimerization or oligomerization of ASG as described for its closest relative, arylsulfatase A (30). ASG eluted as a 63-kDa protein, which corresponds to the monomeric molecular mass also observed in SDS-PAGE.…”
Section: Asg Is Active In the Monomericmentioning
confidence: 72%
“…Arylsulfatase A, the sulfatase with highest homology to ASG, is a lysosomal sulfatase that acts as an octamer at acidic pH (30). Deficiency of arylsulfatase A causes metachromatic leukodystrophy, a lysosomal storage disorder associated with progressive demyelination of the central and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and enzymatic studies of mutants of arylsulfatase A (ASA), in which the FGly was replaced by a serine or alanine, and, namely, the recent solution of the x-ray structure of a bacterial sulfatase at 1.3 Å has shown that the FGly side chain is present as an aldehyde hydrate in the resting state of the enzyme (4, 10 -14). During catalysis one of the two hydroxyls of this geminal diol performs a nucleophilic attack on the sulfur of the substrate's sulfate group leading to a covalently sulfated enzyme intermediate (4,11,12). The second hydroxyl is required for desulfation of the intermediate and for concomitant aldehyde regeneration.…”
mentioning
confidence: 99%
“…It has also been suggested that the nucleophilicity of the O-␥1 atom is enhanced by a possible proton donation to a neighboring aspartic acid residue. In our structural model of the 2-O-sulfatase, this residue would correspond to An S N 2 mechanism has been proposed to follow the above steps and eventually lead to the cleavage of the sulfate ester bond (10,12). In this mechanism, the exocyclic oxygen atom on the leaving substrate may be protonated by water or potentially by neighboring amino acids.…”
Section: Structure-based Homology Modeling Of the 2-o-sulfatasementioning
confidence: 98%
“…The crystal structures of two human lysosomal sulfatases, arylsulfatase A (cerebroside-3-sulfate 3-sulfohydrolase) (9,10) and arylsulfatase B (N-acetylgalactosamine-4-sulfate 4-sulfohydrolase) (11), and a bacterial arylsulfatase from Pseudomonas aeruginosa (12) have been solved. These three sulfatases share an identical alkaline phosphatase-like structural fold (according to the Structural Classification of Proteins Database) 2 composed of a series of mixed parallel and antiparallel ␤-strands flanked by long and short ␣-helices on either side (9 -12).…”
mentioning
confidence: 99%